Natural and long-term preservable anticoagulant property of SiO2 and TiO2 bilayer films - Liu, Xiangqin; Chen, Xiao; Jiang, Hongrui; He, Zikun; Sun, Hong; Huang, Qiongjian; Zhao, Ansha; Huang, Nan; Yang, Ping; Chen, Jiang (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionTitanium dioxide (TiO2) films have been widely studied as blood-contacting materials, but their positively charged surface and low density of surface hydroxyl (-OH) groups result in poor intrinsic anticoagulant properties. Furthermore, TiO2 surfaces readily adsorb carbon-containing contaminants from the environment, causing a rapid decline in anticoagulant performance during storage. Thus, improving TiO2's intrinsic anticoagulant properties and extending its shelf-life remain challenging.MethodsWe fabricated a bilayer film by depositing a ∼40 nm silica (SiO2) overlayer onto TiO2 using unbalanced magnetron sputtering. Surface properties (hydrophilicity, surface charge, and contaminant adsorption) and anticoagulant performance (platelet adhesion after storage) of the resulting SiO2/TiO2 bilayer were characterized.ResultsThe SiO2/TiO2 bilayer exhibited long-lasting hydrophilicity, a net negative surface charge, minimal adsorption of carbonaceous contaminants, and a high surface -OH group content. These characteristics are attributed to the formation of interfacial Si–O–Ti bonds, which in turn led to significantly enhanced anticoagulant properties. Notably, after 15 weeks of storage, platelet surface coverage on the bilayer was less than 30% of that on a TiO2-only film, indicating greatly improved long-term hemocompatibility.DiscussionBy maintaining a hydrophilic, clean surface with abundant surface -OH groups, the SiO2/TiO2 bilayer achieved superior intrinsic anticoagulant performance that was preserved over long-term storage. This bilayer approach addresses key limitations of TiO2, suggesting that SiO2/TiO2 coatings are a promising alternative to pure TiO2 films for blood-contacting devices.